Some considerations on etiology and pathophysiology of oral epidermoid carcinoma - Carla María García San Juan; Magalys S. Salas Rodríguez; José Manuel Gil Milá (Medisur)
Epidermoid carcinoma is a malignant epithelial tumour of unknown etiology, whose incidence worldwide and in American has considerably increased. There is a number of risk factors that could be considered as carcinogenic agents and favor the disease development on the basis a group of pathophysiological mechanisms. Aimed at describing etiological and physiopathlogical factors of oral epidermoid carcinoma, an updated bibliography review was made. Articles were identified through computer searching on data bases SCOPUS and GOOGLE. Thirty original articles were selected. It is concluded that this disease is associated to unhealthy lifestyles on which the Comprehensive general Dentist should influence to decrease its incidence, together with the early diagnosis by implementing properly the National Program of Early Oral Cancer Detection.